(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
The study evaluated teachers’ navigation of artificial intelligence’s ethics in public secondary schools in Awka south local government area of Anambra State. this study was anchored on two research questions. The study adopted descriptive survey research design. The population of the study comprised all the teachers in the 19 public secondary schools in Awka South LGA totaling 604. Stratified simple random technique was used to select 10 schools with 121 teachers. The instrument for the study was designed by the researcher and entitled “Evaluation of Teachers’ Navigation of Artificial Intelligence’s Ethics Questionnaire” (ETNAIEQ). Validity of the instrument was done by three experts in related areas. The reliability of the instrument was carried out using Cronbach Alpha method which yielded co-efficient value of 0.85 which was considered adequate for the study. Administration of the instrument was done by the researcher along with four trained research assistants. Out of 121 copies of the questionnaire distributed, 105 copies were recovered making a total of 86.7% return rate which is rated good for the study. The analysis of the data was done using statistical mean to answer the research questions. It is the findings of the study that teachers are unaware of the artificial intelligence’s ethics in public secondary schools in Awka South LGA. Based on the findings, it is recommended that seminars and conferences be speedily carried out for teachers in public secondary schools on the awareness of navigation of artificial intelligence’ ethics for quality educational delivery process.